State and society in Africa : from construction of the state to social disintegration : a sociological foundation theory of the plural state in Africa - (:unkn) unknown (CCSD, 1995)
Texte intégral accessible uniquement aux membres de l'Université de Lorraine
Keywords: African Research; Reconstruction de l'État-Afrique Noire; Sociologie politique; [SHS.SCIPO]Humanities and Social Sciences/Political science